2017
DOI: 10.4184/asj.2017.11.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Milwaukee Brace Pad Pressure in Adolescent Round Back Deformity Treatment

Abstract: Study DesignIn this prospective study, we measured the pad pressures of the Milwaukee brace in adolescent hyperkyphosis treatment.PurposeWe evaluated the skin-brace interface forces exerted by the main pads of the Milwaukee brace.Overview of LiteratureA fundamental factor associated with brace effectiveness in spinal deformity is pad force adjustment. However, few studies have evaluated the in-brace force magnitude and its effect on curve correction.MethodsInterface forces at four pads of the Milwaukee brace w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…However, these values exceeded the standing position value at maximum tension. Our results are comparable with the study done by Babaee et al, 37 who investigated the action of the Milwaukee brace. This happened when the knee and hip are flexed in the sitting position, pelvic is shifted backward, and thoracolumbar lordosis reduced, and thus interface pressure values also reduced.…”
Section: Discussionsupporting
confidence: 92%
“…However, these values exceeded the standing position value at maximum tension. Our results are comparable with the study done by Babaee et al, 37 who investigated the action of the Milwaukee brace. This happened when the knee and hip are flexed in the sitting position, pelvic is shifted backward, and thoracolumbar lordosis reduced, and thus interface pressure values also reduced.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the Milwaukee brace was applied for both experimental groups monitored during treatment. The Milwaukee brace could extend the trunk because of two pairs of thoracic corrective pads, which apply force anteriorly to the curve apex, and shoulder pads, which use pressure posteriorly through the shoulders 5 . The result of the present study showed the positive effect of bracing on improving thoracic hyperkyphosis, which is in line with results of previous studies 27 .…”
Section: Discussionsupporting
confidence: 91%
“…Corrective exercise (CE) and bracing are considered the two most conventional treatments for thoracic hyperkyphosis 3,5,6 . Bracing is the most effective nonoperative treatment for patients with flexible kyphotic deformity, which has been confirmed in some studies 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations